Structure of copper shaped charge liner evolution law based on die forging process. (March 2020) - Zhang, M Y; Gao, P; Yan, Z F; Tian, T; Cai, W Z; Jia, X B
Abstract: Numerous studies have addressed the effect of grain size of materials on the overall penetrating performance of warheads. However, the use of the forging process to illustrate the grain heat-treatment refining technology has not been reported. In this experiment, the grain size of copper was observed and evaluated during the main processes of preparing copper shaped charge liners using the die forging process. Through this study, the evolution law for the structure of copper shaped charge liners was examined. In the as-cast condition, the grains of the copper ingots were mostly evenly distributed large flaky equiaxed crystal. Pre-forging and die forging make the grains appear more like strips. After the recrystallization heat treatment, the grain size of the copper shaped charge liner was refined and more uniform. Using these results, this study presents an evolution curve for copper shaped charge liners prepared using the forging process. The results can be used as a technical reference to solve the problem of grain size deviation in the production process of copper shaped charge liners.